2013
DOI: 10.2334/josnusd.55.281
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in MMP9 and MMP13 contribute to tooth agenesis in a Brazilian population

Abstract: We investigated the association between polymorphisms in the MMP2 (rs243865), MMP9 (rs17576), and MMP13 (rs2252070) genes with tooth agenesis in humans. Two hundred eighty-five unrelated individuals (202 controls without tooth agenesis and 83 cases with tooth agenesis) were evaluated in a cross-sectional single-center study. The study participants were recruited through the Pediatric Dental Clinics of the Federal University of Rio de Janeiro, Brazil. Genotyping of the selected polymorphisms for MMPs was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
1
1
Order By: Relevance
“…These authors found associations among dental agenesis, MMP-1 (p = 0.007) and MMP-20 (p = 0.03) in Brazilian families. These results disagree with those reported by Antunes et al, 33 who studied the association of polymorphisms in human genes for MMP-2, MMP-9 and MMP-13 with dental agenesis, in 285 non-related individuals en individuos caucásicos con pobres hábitos de higiene oral.…”
Section: Studies In Humanscontrasting
confidence: 57%
See 1 more Smart Citation
“…These authors found associations among dental agenesis, MMP-1 (p = 0.007) and MMP-20 (p = 0.03) in Brazilian families. These results disagree with those reported by Antunes et al, 33 who studied the association of polymorphisms in human genes for MMP-2, MMP-9 and MMP-13 with dental agenesis, in 285 non-related individuals en individuos caucásicos con pobres hábitos de higiene oral.…”
Section: Studies In Humanscontrasting
confidence: 57%
“…Estos autores encontraron asociaciones entre la agenesias dentales, MMP-1 (p= 0,007) y MMP-20 (p= 0,03) en las familias brasileras. Estos resultados son contrarios a los reportado por Antunes y colaboradores, 33 en donde estudiaron la asociación de polimorfismos en genes para MMP-2, MMP-9 y MMP-13 en humanos con agenesias dentales, en 285 individuos no relacionados (202 controles sin agenesia dental y 83 casos con agenesia dental), donde no encontraron asociación significativa para el genotipo MMP-2, y encontraron una relación significativa de agenesias dentales asociadas a los genotipos de MMP-9 y MMP-13.…”
Section: Studies In Humansunclassified
“…Genetic modifications may be associated to a greater or lesser degree with the production of these molecules, or interfere in their physiology (5). Polymorphism in the MMP13 gene was previously associated with the development of colorectal cancer, aneurysm of the abdominal aorta, tooth agenesis and caries (11,23). In addition, polymorphisms in the TGFB3 gene were associated with non-syndromic cleft lip and development of tooth agenesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, Brazil is a pioneer in genetic studies in dentistry with a high number of publications in this area, with international collaborations for studies in hypodontia. Numerous Brazilian studies on genetics in dentistry have identified the association of genetic variations in MMP9 and MMP13 (Antunes et al., ), FGF3 (Vieira et al., ), TGFB3, and BMP4 (Antunes et al., ), MMP1 and MMP20 (Küchler et al., ), MSX1 and PAX9 (Lopez et al., ) with tooth agenesis, in a Brazilian population.…”
Section: Hypodontiamentioning
confidence: 99%